Aortic aneurysm dissection – diagnosis may be hard to make - Monteiro, Patrícia (2009)
The authors report the case of a 70-year-old woman admitted with intense asthenia, anaemia and increased erythrocyte sedimentation rate following an acute and sudden episode of anterior thoracic pain six weeks before. Clinical investigation was conclusive for the diagnosis of subacute aortic dissection type A. Surgical repair and placement of endovascular prosthesis was performed, allowing the disappearance of general manifestations.Aortic dissection is usually associated with an acute and highly symptomatic clinical presentation. This case report illustrates the diagnostic difficulties when aortic dissection presents with prominent features characterized by systemic symptoms and elevated acute phase response laboratory parameters. Knowledge of this atypical presentation, a high degree of suspicion, and investigation using an adequate imaging method will help improve our capability for a correct diagnosis of this entity.